Critical analysis of Lean Construction measuring tools - Lucena, Arthur Felipe Echs; De Mori, Luci Mercedes (Brazilian Journal of Operations & Production Management, 2018)
The Lean Construction philosophy emerged to assist overcome the challenges in optimizing the productive processes of companies. As an effort to quantify the application degree of Lean philosophy in the civil construction companies, several measurement tools were created. In order to discuss the effectiveness of these tools into measuring the presence of the Lean philosophy in construction sites, the present study performed a critical analysis of its methodological procedures, based on four aspects: ‘questionnaires and forms’, ‘answering system’, ‘data collection methodology’, and ‘results’. Although it was not possible to investigate measuring tools from other countries, it was concluded that, among Brazilian methods, the one developed by Pereira (2012) is the most suitable for use since it presented just few problems in its formulation. This way, it is possible to do the intended measurement with assertiveness, substantially contributing to civil construction development.